The Preventive Effects of Posterior Pericardiotomy with Intrapericardial Tube on the Development of Pericardial Effusion, Atrial Fibrillation, and Acute Kidney Injury after Coronary Artery Surgery: A Prospective, Randomized, Controlled Trial - Kaya, Mehmet; Utkusavaş, Ayfer; Erkanlı, Korhan; Güler, Salih; Kyaruzi, Mugisha; Birant, Ali; Karaçalılar, Mehmet; Akkuş, Murat; Bakır, İhsan (The Thoracic and Cardiovascular Surgeon, 2016)
Background Pericardial effusion (PE), atrial fibrillation (AF), and acute kidney injury (AKI) are commonly found after coronary artery surgery. These adverse events may also be interwoven in the postoperative period. In this prospective study, we investigated whether posterior pericardiotomy (PP) with intrapericardial tube positioned along the right atrium (pericardial space intervention) is effective in the prevention of these adverse events.Methods The patients were randomly distributed to the study and control groups. The study group consisted of patients with pericardial space intervention, whereas the control group consisted of patients without pericardial space interventions. In all patients, a straight tube was placed in the anterior mediastinum and an angled tube was placed into the left hemithorax.Results A total of 210 patients were studied: 107 in the control group and 103 in the study group. Statistically significant results were obtained in the amount of PE, cardiac tamponade, AF (p = 0.019), and AKI during the postoperative period, in favor of the study group. Length of hospital stay was significantly shorter in the study group (6.11 ± 2.31, p = 0.009).Conclusion The PP with intrapericardial tube approach is safe, easy, and effective in the prevention of PE, cardiac tamponade, and AF. The use of this approach may reduce the risk of developing AKI during the postoperative period. Besides, this technique also reduces the length of hospital stay.
Keywords: posterior pericardiotomy; intrapericardial tube; pericardial effusion; kidney injury; atrial fibrillation